Разработка технологии получения 123 I по реакции 122 Te(d,n) - Агалаков Ю. В.; Большаков А. М. Алексей Михайлович; Гарапацкий А. А. Александр Александрович; Головков В. М. Владимир Михайлович; Комов А. И. Александр Иванович; Скуридин В. С. Виктор Сергеевич; Шеин В. В. (2006, 2006)
В фонде НТБ ТПУ отсутствует